Global External Stochastic Stabilization of Linear Systems with Input Saturation: An Alternative Approach - Qingling Wang (Complexity)
This paper presents results concerning the global external stochastic stabilization for linear systems with input saturation and stochastic external disturbances under random Gaussian distributed initial conditions. The objective is to construct a class of control laws that achieve global asymptotic stability in the absence of disturbances, while guaranteeing a bounded variance of the state for all the time in the presence of disturbances. By using an alternative approach, a new class of scheduled control laws are proposed, and the global external stochastic stabilization problem can be solved only through some routine manipulations. Furthermore, the reported approach allows a larger range of the design parameter. Finally, two numerical examples are provided to validate the theoretical results.